Key Plant, Key Pests: Camellia - Juanita Popenoe; Caroline G Roper Warwick; Brian J. Pearson (EDIS)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists and landscape professionals to help identify common pests associated with common Florida fauna. This publication, the second in the Key Plant, Key Pests Series, helps identify the most common pests found on the Camellia. This publication provides information and general management recommendations for algal leaf spot, dieback, twig blight or canker, flower blight, wet root rot diseases, root rots, aphids, scale, spider mites and nutrient deficiencies. https://edis.ifas.ufl.edu/ep558